(untitled) (Ius Novum, 2025)
The subject of this article is the issue of prevention the abuse of the right to a court. The author draws attention to the fact that the phenomenon of the abuse of the right to a court and its prevention have accompanied the development of law and legal regulations since ancient times. The article presents the issue of the abuse of the right to a court in relation to the Roman sacramentum and indicates the essence of contemporary SLAPPs (Strategic Lawsuits Against Public Participation) and ways of counteracting them. Sacramentum was an institution of procedural law and has deep roots in the religious tradition of ancient Rome and symbolic meaning, while SLAPPs are a modern, undesirable phenomenon related to the procedural and financial aspects of the legal system. The article also indicates the relationships, similarities and differences between the ancient Roman sacramentum and modern SLAPPs, as well as an attempt to answer the question whether the use of the equivalent of the Roman institution of sacramentum could effectively limit contemporary SLAPPs.